Circulating Biomarkers and Cardiac Structure and Function in Rheumatoid Arthritis - Kobayashi, Masatake; Ferreira, Maria Betânia; Costa, Rita Quelhas; Fonseca, Tomás; Oliveira, José Carlos; Marinho, António; Carvalho, Henrique Cyrne; Girerd, Nicolas; Rossignol, Patrick; Zannad, Faiez; Rodrigues, Patrícia; Ferreira, João Pedro (Frontiers in Cardiovascular Medicine, 2021)
Background: Rheumatoid arthritis (RA) increases the risk for abnormalities of the cardiac structure and function, which may lead to heart failure (HF). Studying the association between circulating biomarkers and echocardiographic parameters is important to screen RA patients with a higher risk of cardiac dysfunction. Aims: To study the association between circulating biomarkers and echocardiographic parameters in patients with RA. Methods: Echocardiography was performed in 355 RA patients from RA Porto cohort and the associations between echocardiographic characteristics and 94 circulating biomarkers were assessed. The findings were externally validated in the MEDIA-DHF (392 HFpEF patients) and STANISLAS (1,672 healthy population) cohorts. Results: In the RA Porto cohort, mean age was 58±13 years, 23% were male, and mean RA duration was 12±10 years. After adjustment and multiple test correction, left ventricular mass indexed (LVMi), left atrial volume indexed (LAVi) and E/e’ were independently associated with biomarkers reflecting extracellular matrix remodeling (i.e., BMP9, PGF), congestion (i.e., NT-pro BNP, ADM), inflammation (i.e., PTX3, TNFRSF11A), and myocardial injury (e.g., Troponin). Greater LVMi (HR [95%CI] per 1g/m²=1.03 [1.02-1.04], p<0.001), LAVi (HR [95%CI] per 1ml/m²=1.03 [1.01-1.06], p<0.001), and E/e’ (HR [95%CI] per 1=1.08 [1.04-1.13], p<0.001) were associated with higher rates of cardiovascular events. These associations were externally replicated in patients with HFpEF and asymptomatic individuals. Conclusions: Circulating biomarkers reflecting extracellular matrix remodeling, congestion, inflammation, and myocardial injury were associated with underlying alterations of cardiac structure and function. Biomarkers might be used for the screening of cardiac alterations in patients with RA.